THE INFLUENCE OF SOCIAL FACTORS ON STUDENTS’ ACHIEVEMENT IN LEARNING ENGLISH - Farianti, Suci (UPT. Pengembangan Bahasa IAIN Zawiyah Cot Kala Langsa, 2018)
The research focused on the social factors which can influence the students’ achievement in learning English. Social factors are believed as the factors which play a crucial role in language learning and it can give impacts on foreign language learning. In this case, this research was conducted to investigate the impacts of social factors of parents’ economic level, Parents’ education level, parents’ occupation level and the environment on students’ achievement in learning English as a foreign language. The objects of the research were 10 students with special need and their parents at the eighth grade of SLB Negeri Pembina Aceh Tamiang. In conducting the data, the test and the questionnaire were designed. The twenty question items of the test were given to the students and an eighteen item of questionnaire were given to the parents’ to find out the require information on the social factors. In addition, in analyzing the data, all available data were processed by SPSS 17.0 for descriptive, correlation, ANOVA, and predictive analysis. Furthermore, based on the finding and the result of the research, the hypothesis (H0) of the research was rejected. In other word, there was no a significant correlation between social factors namely parents’ economic level, parents’ education level, parent’s occupation level and environment on students’ achievement in learning English. Therefore, it can be stated that the variety of the students’ scores were not influenced by the social factors discussed on this research in which it was probably influenced by other factors such as the personality of the students, the students’ disability, etc.